Dissecting the Ghana roselle (hibiscus sabdariffa var. Altissima) accessions for genetic diversity using agro-morphological evaluation - Ankrah, Nii Ayi (KNUST, 2026)
A thesis submitted to the department of biochemistry and biotechnology, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirement for the award of Master of Science in biotechnology